Gender and Health Status Response to Long-Term Oxygen Therapy in COPD Patients - Dela Coleta, Karina [UNESP]; Lima, Daniela F. [UNESP]; Tanni, Suzana E. [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Godoy, Ilda de [UNESP]; Godoy, Irma de [UNESP] (Ediciones Doyma S A, 2011)
Introduction: The association of gender with health status (HS) response to long-term oxygen therapy (LTOT) in very severe COPD is unclear. The aims of this study were: (1) to compare dyspnea perception and HS between male and female with very severe COPD at baseline and (2) to provide a prospective assessment of HS response to LTOT, according to gender.Patients and methods: Hypoxemic COPD (n =97, age: 65.5 +/- 9.6 years, 53% males) were enrolled in a prospective longitudinal study over 12 months or until death. St. George's Respiratory Questionnaire (SGRQ) and baseline dyspnea index (BDI) were assessed.Results: At baseline, HS impairment and dyspnea sensation were similar between genders. After 12 months of LTOT, women presented improvement in symptom (64.1 +/- 120.6 versus 40.6 +/- 122.9; P < 0.0001) and total SGRQ scores. Men also showed improvement in symptoms after 12 months (62.7 +/- 23.3 versus 49.6 +/- 22.8; P < 0.0005); however, they presented deterioration of activity, impact and total scores during the study period, with markedly decline of activity domain (68.5 +/- 20.0 versus 75.9 +/- 16.9; P = 0.008). BDI did not show significant difference by gender over the study period.Conclusions: Our results show that the HS course in very severe COPD patients differs according to gender, as females show greater response longitudinally to LTOT. (C) 2010 SEPAR. Published by Elsevier Espana, S.L. All rights reserved.
Keywords: COPD; Gender; Health status; LTOT